Totalitarny islamizm czy totalny islam? Irracjonalny lęk czy uzasadniony strach? Mirosława Sadowskiego integralna i kontekstowa analiza szariatu - Michalak, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the article, the author presents his reflections on the publications of Mirosław Sadowski, the book Islam. Religia i prawo (Islam. Religion and law) and the article “Czy islam ma charakter totalitarny?” (Is Islam of a totalitarian nature?). The main references are the systemic nature of Islam (totalitarianism and total theocracy) and the problem of political correctness. The text elaborates on selected theses, characteristic of current research, which pays homage to selective analysis based on the paradigm of Islamophobia. The scientific narrative consisting of the reduction of complex phenomena to one code has been criticized.
Keywords: Islam; szariat; totalitaryzm; totalna teokracja; islamosceptycyzm; islamofobia; poprawność polityczna